Finite size scaling in the heterogeneous reaction 2A + B2 −→ 2AB - Hernández Guiance, Sabrina Noemí (2022)
In the present paper we extend the exact solution previously obtained for the heterogeneous catalytic reaction 2A+B2 → 2AB on small 2×2 domains, to arbitrary lattice sizes (N × N) and calculate the average number of reactive steps necessary to poison the lattice first,< t >. We determine < t > as a function of N through Monte Carlo simulations previously contrasted with the exact solution in 2 × 2 lattices. We show that < t > follows a power law with N, without appreciable transient behaviors, and a scale factor (ν) dependent on the two parameters of the model, the sticking coefficient probability s and the desorption probability pd. The dependence of ν on both s and pd is determined.